The Australian Royal Commission into Institutional Responses to Child Sexual Abuse: Dreaming of Child Safe Organisations? - Budiselik, Bill; Crawford, Frances; Chung, Donna (M D P I AG, 2014)
On 12 November 2012 the then Australian Prime Minister Julia Gillard announced she was recommending to the Governor General the establishment of a Royal Commission into Institutional Responses to Child Sexual Abuse. Following inquiries in Australia and elsewhere much is already known about institutional and inter-institutional child protection failures and what is required to address them. That Australia’s national government has pursued another abuse inquiry with terms of reference limited to institution-based (excluding the family) sexual abuse is of interest given the lack of political will to enact previous findings and recommendations. This article examines the background to the Government’s announcement, the Commission’s terms of reference and some of its settings, and literature on the nature of royal commissions across time and place. After the lack of success in implementing the recommendations of previous inquiries into how to better protect Australia’s children, the question is: how will this Royal Commission contribute to Australian child protection and safety? Will the overwhelming public support generated by “truth speaking to power” in calling for this inquiry translate into action?